2022
DOI: 10.3389/fbioe.2022.983510
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian middle ear mechanics: A review

Abstract: The middle ear is part of the ear in all terrestrial vertebrates. It provides an interface between two media, air and fluid. How does it work? In mammals, the middle ear is traditionally described as increasing gain due to Helmholtz’s hydraulic analogy and the lever action of the malleus-incus complex: in effect, an impedance transformer. The conical shape of the eardrum and a frequency-dependent synovial joint function for the ossicles suggest a greater complexity of function than the traditional view. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 216 publications
0
0
0
Order By: Relevance
“…The full-scale experiments connected with the investigation of drum membrane can be conducted, with certain accuracy, with the help of the formulas obtained in this work. The general provisions connected with the middle ear and drum membrane mechanics are described in the overview work [23], where it is demonstrated that the drum membrane can be interpreted as a mechanical membrane. In [24], the authors propose the system of two ordinary differential equations as a model of drum membrane oscillations, and the solution of this system is defined by an integral operator.…”
Section: Oscillations Of Circular Membranesmentioning
confidence: 99%
“…The full-scale experiments connected with the investigation of drum membrane can be conducted, with certain accuracy, with the help of the formulas obtained in this work. The general provisions connected with the middle ear and drum membrane mechanics are described in the overview work [23], where it is demonstrated that the drum membrane can be interpreted as a mechanical membrane. In [24], the authors propose the system of two ordinary differential equations as a model of drum membrane oscillations, and the solution of this system is defined by an integral operator.…”
Section: Oscillations Of Circular Membranesmentioning
confidence: 99%